Reserva legal em condomínio como alternativa à recomposição da vegetação nativa no estado de Minas Gerais - Lima, Elaine Cristina Ribeiro (2008)
This study intends to comprehend many legal controversies, environmental and economical, that involve the legal reserve institute of rural properties that lack native vegetation, mainly the legal reserve set in condominium, with RPPN, according to the legislation of Minas Gerais state. In Minas Gerais, cornerstone of this study, law n. 14.309/2002 (state Forest Code) while determines the institution of legal reserve in 20% of the rural property, in its article 17, brings specific hypothesis of compensation to properties that lack native vegetation. Among these alternatives, we point out the one described in incise VI, which allows the owners the acquisition of non contiguous properties (even in another basin) in condominium, which area is equivalent to the total sum of the legal reserve of all the co-owners with the institution of the Natural Property Private Reserve (RPPN). This hypothesis of compensation will be the main object of this study, which has been developed using the techniques of documental and bibliographic research, and also the intensive direct field observation and interviews. Besides the controversy that surrounds the debate regarding the determination or not to institute legal reserve in properties that lack native vegetation, with antagonist opinions about the legal interpretation, there is one about the constitutionality of this rule mentioned, considering that Minas Gerais state has concurrent jurisdiction to rule. This study will also point out the environmental impact caused by this compensatory alternative brought by the Minas Gerais law, its positive and negative aspects. It will also be presented economical data regarding the adoption of the compensatory legal reserve and its impact in the financial lives of the rural property owners and of the cities involved, under the analyses of economical activity reduction and environmental ICMS payment.